2005
DOI: 10.4049/jimmunol.175.6.4000
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functions of Tyrosine Kinase 2 in the Antiviral Defense against Murine Cytomegalovirus

Abstract: We have recently reported that tyrosine kinase 2 (Tyk2)-deficient mice have a selective defect in the in vivo defense against certain viruses. In our current study we show that Tyk2 is essential for the defense against murine CMV (MCMV). In vivo challenges with MCMV revealed impaired clearance of virus from organs and decreased survival of mice in the absence of Tyk2. Our in vitro studies demonstrate that MCMV replicates to dramatically higher titers in Tyk2-deficient macrophages compared with wild-type cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 63 publications
3
61
1
Order By: Relevance
“…Further, IFN-␤ constitutively expressed prior to any stimulation with IFN-␥ has been shown to be necessary to maintain STAT1 levels for IFN-␣R1 blockage by antibodies, and it has been shown that depletion of IFN-␤ reduces STAT1 levels (25). In agreement with those studies, reduced STAT1 and STAT2 levels have been reported in IFN-␣R1 Ϫ/Ϫ and Tyk2 Ϫ/Ϫ BMDMs (39,75,76). Furthermore, in the study by Zimmermann et al (2005), it was shown that IFN-␣/␤ contributes to an IFN-␥-induced refractory state in MEFs and that MCMV counteracts this mechanism through the virus-encoded factor M27.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Further, IFN-␤ constitutively expressed prior to any stimulation with IFN-␥ has been shown to be necessary to maintain STAT1 levels for IFN-␣R1 blockage by antibodies, and it has been shown that depletion of IFN-␤ reduces STAT1 levels (25). In agreement with those studies, reduced STAT1 and STAT2 levels have been reported in IFN-␣R1 Ϫ/Ϫ and Tyk2 Ϫ/Ϫ BMDMs (39,75,76). Furthermore, in the study by Zimmermann et al (2005), it was shown that IFN-␣/␤ contributes to an IFN-␥-induced refractory state in MEFs and that MCMV counteracts this mechanism through the virus-encoded factor M27.…”
Section: Discussionsupporting
confidence: 62%
“…Type I IFNs are known to effectively inhibit MCMV replication in NIH 3T3 cells and BMDMs (26,76). It is noteworthy that in our study we did not observe a prototypic type I response involving antiviral factors such as PKR, RNase L, ISG-15, or oligoadenylate synthetase.…”
Section: Discussioncontrasting
confidence: 51%
“…Conversely, DCs are important in NK cell activation and the initiation of the specific immune response (11). Upon MCMV infection in vivo, antigen-presenting cells such as conventional dendritic cells (cDCs), plasmacytoid dendritic cells (pDCs), and macrophages are key producers of type I IFN and other proinflammatory cytokines (1,12,25,48,57). However, pDCs seem to play a central role in mounting a protective type I IFN response (25,57).…”
Section: Secretion Of Ifn-␣ and Other Proinflammatory Cytokines Corrementioning
confidence: 99%
“…Mice deficient for Tyk2 (Tyk2 À/À mice) are viable and fertile but were described to have defects in type I IFN, IL12, and also type II IFN (IFNg) signaling (11,12). Tyk2 À/À mice show an increased susceptibility to various pathogens (11,(13)(14)(15) but are resistant against lipopolysaccharide (LPS)-induced endotoxin shock (16). In addition, Tyk2 is a key regulator for Th1/Th2 balance (17).…”
Section: Introductionmentioning
confidence: 99%